Ácido D-glucônico e sua relação com a micobiota de uvas produzidas em Santa Catarina - Nunes, Estela de Oliveira (2008)
D-gluconic acid concentration in musts and wines is natural of acid sources, being produced by filamentous fungi and/or bacteria. Aspergillus, Botrytis, and Penicillium sp., oxidize to glucose to produce D-gluconic acid, that is not used by yeasts or bacteria and can be used as a fruit deterioration indicator. Since the detection of ochratoxin A (OTA) in juices and wines related studies to mycobiota of the grapes, under the ochratoxigenic potential point of view has been being evaluated. The present study had the goal of evaluating the grapes sanity degree produced in Santa Catarina in the crops 2005/2006, using the D-gluconic acid concentration as indicator. D-gluconic acid correlation between OTA, mycobiota and population of Aggregate A. niger went 0,017; 0,004 and 0,008, respectively, reflecting the low correlation presented with OTA. For the population of Botrytis the decisive factor was 0751, or only 24.9% of the variation can not be explained, since the mycobiota with the relationship was very low, reinforcing the hypothesis of association with other factors such as the presence of bitter rot.